Multiplicity and transverse momentum evolution of charge-dependent correlations in pp, p–Pb, and Pb–Pb collisions at the LHC - Adam, J.; Adamovã, D.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aiola, S.; Akindinov, A.; Alam, S.N.; Aleksandrov, D.; et al. (Springer, 2016)
We report on two-particle charge-dependent correlations in pp, p-Pb, and Pb-Pb collisions as a function of the pseudorapidity and azimuthal angle difference, [Formula: see text] and [Formula: see text] respectively. These correlations are studied using the balance function that probes the charge creation time and the development of collectivity in the produced system. The dependence of the balance function on the event multiplicity as well as on the trigger and associated particle transverse momentum ([Formula: see text]) in pp, p-Pb, and Pb-Pb collisions at [Formula: see text] 7, 5.02, and 2.76 TeV, respectively, are presented. In the low transverse momentum region, for [Formula: see text] GeV/c, the balance function becomes narrower in both [Formula: see text] and [Formula: see text] directions in all three systems for events with higher multiplicity. The experimental findings favor models that either incorporate some collective behavior (e.g. AMPT) or different mechanisms that lead to effects that resemble collective behavior (e.g. PYTHIA8 with color reconnection). For higher values of transverse momenta the balance function becomes even narrower but exhibits no multiplicity dependence, indicating that the observed narrowing with increasing multiplicity at low [Formula: see text] is a feature of bulk particle production.
Keywords: Pseudorapidity; Physics; Multiplicity (mathematics); Large Hadron Collider; Particle physics; Nuclear physics; Transverse plane; Charged particle; Geometry; Quantum mechanics; Mathematics; https://purl.org/pe-repo/ocde/ford#1.03.04